2001
DOI: 10.1096/fj.01-0123com
|View full text |Cite
|
Sign up to set email alerts
|

17β‐Estradiol inhibition of NADPH oxidase expression in human endothelial cells

Abstract: We investigated the hypothesis that the antiatherosclerotic effect of 17beta-estradiol (E2) is due to a shift in the nitric oxide (NO)/superoxide (O2-) balance in the vessel wall, thereby increasing the bioavailability of NO. In human umbilical vein cultured endothelial cells, E2 (1-100 nmol/l), but not 17alpha-estradiol, caused a time- and concentration-dependent decrease in expression of the NADPH oxidase subunit gp91phox (up to 60% inhibition at both the mRNA and protein level). This effect was prevented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(126 citation statements)
references
References 54 publications
6
117
3
Order By: Relevance
“…Determination of Superoxide Formation-Generation of superoxide in the cultured endothelial cells was estimated as described previously (17). Phorbol 12,13-dibutyrate was used as a positive control and changes in the cells capacity to generate superoxide in response to acute (1-10 min) and prolonged (6 -12 h) exposure to IL-10 (2 ng/ml) or a combination of pro-inflammatory cytokines (60 units/ml IL-1␤, 1000 units/ml TNF-␣, and 1000 units/ml IFN␥) were monitored.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of Superoxide Formation-Generation of superoxide in the cultured endothelial cells was estimated as described previously (17). Phorbol 12,13-dibutyrate was used as a positive control and changes in the cells capacity to generate superoxide in response to acute (1-10 min) and prolonged (6 -12 h) exposure to IL-10 (2 ng/ml) or a combination of pro-inflammatory cytokines (60 units/ml IL-1␤, 1000 units/ml TNF-␣, and 1000 units/ml IFN␥) were monitored.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, estrogens reduce both the monocyte and neutrophil adhesion to the endothelial monolayer and the transendothelial migration of monocytes under in vitro conditions (Alvarez et al 2002, Geraldes et al 2006. In addition, exposure of endothelial cells to estrogens suppresses the NADPH oxidase activity and thereby the intracellular production of reactive oxygen species (ROS), which is instrumental for the expression of adhesion molecules in response to pro-atherogenic factors (Wagner et al 2001). Experiments using ER agonists and antagonists point to both ERa and ERb as mediators of suppressing effects of E 2 on endothelial activation (Mukherjee et al 2003, Mori et al 2004, Geraldes et al 2006, though again these effects could also be observed in the presence of 2-ME (Kurokawa et al 2007, Dubey & Jackson 2009).…”
Section: Mechanisms Underlying Anti-atherogenic Effects Of Estrogens mentioning
confidence: 99%
“…A recent study in normotensive women showed that endothelial dysfunction secondary to acute endogenous estrogen deprivation is strongly linked to a reduction in the bioavailability of ·NO [67]. Moreover, E 2 can attenuate O 2 −· formation in phagocytes [68] and endothelial cells [6]. In summary, the reduction in O 2 −· formation combined with the salutary effects of ·NO may account for decreased LDL oxidative modification by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…OSS is characterized as bidirectional net zero forward flow that commonly occurs within vascular bifurcations and branching points. OSS is a potent stimulus for proatherogenic expression of adhesion molecules and chemokines [4,5] and enhancing vascular NADPH oxidase activity [6,7]. Our previous studies demonstrated that OSS increased production of superoxide anion (O 2 −· ) [7,8] and oxidative modification of low density lipoprotein (LDL) [5].…”
Section: Introductionmentioning
confidence: 99%